Deer Creek Drive : a Reckoning of Memory and Murder in the Mississippi Delta - Lowry, Beverly (New York : Alfred A. Knopf, 2022)
"In 1948, in the most stubbornly Dixiefied corner of the Jim Crow south, society matron Idella Thompson was viciously murdered in her own home: stabbed some hundred and fifty times with pruning shears, she was left face-down in one of the bathrooms. Her daughter, Ruth Dickins, was the only other person in the house. She told authorities a Black man she didn't recognize fled the scene, but no evidence was uncovered. When Dickins was convicted and sentenced to a life in prison, the community exploded. Petitions were drafted, signed, and circulated, pleading for her release, and after only five years, she was indeed set free. The governor granted Ruth Dickens an indefinite suspension. Beverly Lowry-who was ten at the time of the murder-continued to investigate what happened decades ago on the most prestigious street in Leland, Mississippi, and she reflects on what her working class childhood in the south means today. With brilliant reporting and irresistible prose, Deer Creek Drive tells the story of that unspeakable murder within the wider context of race and class, and sheds light on what it was like to grow up white in the Mississippi Delta during the last years of school segregation"--
Includes bibliographical references (pages 347-354).
Keywords: Thompson, Idella, -- 1879-1948.; Dickins, Ruth Thompson, -- 1906-1996.; Murder -- Mississippi -- Leland -- Case studies; Leland (Miss.) -- Social conditions -- 20th century; Leland (Miss.) -- Race relations; True crime stories